Growth of protectionism in India : a critical appraisal of the policy of protection in India - Verma, Yogendra Prasad (New Delhi : S. Chand, 1974)
This book propose to examine, as case study, the effectiveness o the policy of protection, in India, and to identify the directions in which it needs to be improved upon.
Originally presented as the author's thesis, Patna University, 1971.
Bibliography: p. 241-245.
osa;12/07/18
Loans
Keywords: Protectionism; Protection policy; India